2022
DOI: 10.12965/jer.2244080.040
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of elongation band exercise on the upper limb strength and range of motion among older adults

Abstract: An elongation band (EB) is used to improve the physical strength of older adults. However, the evidence of its effect on the upper limb is a deficiency. This study investigated the effectiveness of EB exercises on upper limb function in the elderly. Participants were divided into two groups: EB (n=16) and control (n=14). The EB group performed exercises in a sitting position using an EB while the control group performed active stretching exercises without bands. The exercise regimen consisted of four shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is well known that exercise can reduce the fall rate in older adults 3 ) . Several studies have reported that resistance band exercise has proven to be useful in improving leg muscle strength and balance in older adults 4 , 5 , 6 , 7 , 8 ) . The intensity of the natural load can be adjusted, making this form of exercise useful for strengthening muscles in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that exercise can reduce the fall rate in older adults 3 ) . Several studies have reported that resistance band exercise has proven to be useful in improving leg muscle strength and balance in older adults 4 , 5 , 6 , 7 , 8 ) . The intensity of the natural load can be adjusted, making this form of exercise useful for strengthening muscles in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Upper limb strength training is essential in sports performance [1,2] and in improving autonomy for the activities of daily living [3,4].…”
Section: Introductionmentioning
confidence: 99%